Islamic Religious Education in Forming Muslim Identity in the Modern Era - Ulum, Anharul; Asy’arie, Bima Fandi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
In the modern era, Muslim identity develops as a result of complex interactions between religion, culture, technology and the social environment. This identity reflects the deeply rooted Islamic values inherent in every individual. Changes in the social environment, especially in the digital world, also have a significant influence in shaping Muslim identity. This research uses a qualitative approach with a literature study method. In this case, the author collected library data from Google Scholar. The results of this research, first, are that high school students in the contemporary era are educated as shown by their critical attitude, but they do not have Islamic character which is reflected in their behavior. Second, it is felt that the implementation of Islamic religious education in schools has not been optimal in forming Muslim identity, this is indicated by the fact that knowledge and good behavior at school are not carried over into its application in society. Third, the synergy between educational institutions and students' parents is a perfect combination concept in forming the identity of the Muslim generation in the contemporary era. Through good intense communication with students' parents and innovative efforts by teachers, it is hoped that the Islamic values obtained at school can be applied by students in their daily lives, thereby creating an environment where Islamic religious values become an integral part of students' Muslims identity.